Implementation of Public Information Disclosure Policy at LPP RRI Gorontalo - Abdul Gaffar; Yanti Aneta; Alexander H. Badjuka (Journal of Political and Governance Studies, 2026)
Background Public information disclosure is an essential prerequisite for promoting transparent and accountable governance, as mandated by Law Number 14 of 2008 on Public Information Disclosure in Indonesia. In this context, LPP RRI Gorontalo, as a regional public broadcasting institution, has an obligation to provide public information services through the Information and Documentation Management Officer (PPID). However, in practice, the implementation of public information disclosure policy within the institution has not yet been fully optimal. This study aims to examine the implementation of public information disclosure policy at LPP RRI Gorontalo using Edward III’s policy implementation theory. Methods The research employed a qualitative approach with a single case study design. Data were collected through semi-structured in-depth interviews, non-participant observation, and document analysis. Informants were selected purposively and consisted of 11 internal informants and 5 external informants. Results The findings show that the implementation of public information disclosure policy at LPP RRI Gorontalo has been carried out but has not yet operated optimally. In the communication dimension, policy directives and standard operating procedures are available, but technical understanding among implementers remains uneven. In the resources dimension, basic facilities are available, although human resource capacity and archive digitalization still require strengthening. In the disposition dimension, implementers have demonstrated basic commitment, although service orientation remains largely administrative. Meanwhile, in the bureaucratic structure dimension, formal role distribution has been established, but inter-unit coordination and the clarity of service procedures for the public still require improvement. Conclusion This study concludes that successful implementation of public information disclosure depends not only on the existence of regulations and formal institutional structures, but also on the organization’s capacity to translate policy into information services that are accessible, orderly, responsive, and sustainable.